Refining the Laurentide Ice Sheet at Marine Isotope Stage 3: A data-based approach combining glacial isostatic simulations with a dynamic ice model. (1st September 2018) - Pico, T.; Birch, L.; Weisenberg, J.; Mitrovica, J.X.
Abstract: While glacial geologic records track the retreat history of the Laurentide Ice Sheet, constraints on the ice-sheet build-up history are more elusive. As the Laurentide Ice Sheet expanded to its maximum extent at the Last Glacial Maximum (26 ka), it erased most evidence of previous glaciations. However, an increasing number of dated, non-glacial deposits point to a relatively confined Laurentide Ice Sheet during Marine Isotope Stage 3 (MIS 3; 60-26 ka), suggesting rapid ice growth rates leading to the Last Glacial Maximum. In this study we demonstrate that predictions of relative sea-level change due to glacial isostatic adjustment involving a late and rapid growth of the Laurentide Ice Sheet are consistent with sea-level bounds associated non-glacial deposits of MIS 3 age in Canada. We also run a simple dynamic ice model that adopts the paleotopography generated from the glacial isostatic adjustment simulation and show that, using accumulation rates similar to that of the present-day Arctic, rapid glaciation rates starting at mid-MIS 3 (44 ka) are predicted. Highlights: Glacial isostatic adjustment simulations consistent with MIS 3 relative sea-level bounds in Canada. Using a simple dynamic ice model we predict rapid glaciation rates starting at mid-MIS 3 (44 ka). Results support a reduced Laurentide Ice Sheet during MIS 3, implying a rapid growth of the ice sheet leading into the Last Glacial Maximum.